STUDYING CONTROL EQUIPMENT IN THE AUTOMOBILE MANUFACTURING PROCESS (Neo Scientific Peer Reviewed Journal, 2023)
This article discusses methods of testing safety features in the automotive manufacturing process, the study of control inspection equipment, and the issuance of recommendations.